The Impact Of Parental Verbal Violence On Children's Self-Confidence Level At Al-Irsyad Kindergarten, Tanak Sebang In Academic Year 2024/2025 - Musliana, Liza; Ramzi, Muhajirin; Arzani, M. (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract This research explores the influence of parental verbal abuse on the self-confidence of early childhood students at TK Al Irsyad, located in Dusun Tanak Sebang, Desa Salut. Verbal abuse, such as yelling, harsh criticism, or giving negative labels, is an emotional form of violence that can harm a child's psychological development. A qualitative approach with a case study method was used in this study. Participants included children exposed to verbal mistreatment by parents, and teachers were involved as supporting informants. Data were collected through interviews, observations, and documentation. The findings indicate that children frequently subjected to verbal abuse often show low self-esteem, reluctance to communicate, and reserved behavior. The study highlights the importance of collaboration between parents and educators in fostering healthy, supportive communication to help children grow with confidence.